Quotation from the Prophet’s hadith for linguists - Alsharafat, Fayyad Talab Muraibei (Journal of Humanities & Social Sciences, 2022)
The study dealt with the subject of linguists’ quotation from the Prophet’s hadith as one of the sources from which the Arabs drew the rules of the language, and based them according to these phenomena, and the opinion of the ancient and modern Arab linguists by citing the noble hadith. There are some ancient linguists who were attributed to them for their refusal to cite the hadith, but they did not raise this issue, and did not discuss the principle of invoking the hadith, and therefore they did not declare their refusal to cite the hadith. Then try to explain it. It has become clear to us that the most correct among scholars is to cite the noble hadith because the Messenger- may God’s prayers and peace be upon him- was the most eloquent of those who spoke the opposite, and that there are many reasons to doubt the authenticity of what was attributed to the ancients about their refusal to cite the hadith, and there are evidences that confirm in a way It is certain that they used to cite the hadith and build their bases on it, whether they worked with language or grammar or both.